( x^2 + 3 )^2 - ( x + 3 ).( x - 3 ).( x^2 + 9 )
giúp mình với :((
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\left(x^2-9\right)^2-\left(x-3\right)\left(x+3\right)\left(x^2+9\right)=\left(x^2-9\right)^2-\left(x^2-9\right)\left(x^2+9\right)\)
\(=x^4-18x^2+81-x^4+81=-18x^2+162\)
b, \(\left(x^2+x-3\right)\left(x^2-x+3\right)=\left[x^4-\left(x-3\right)^2\right]\)
\(=x^4-x^2+6x-9\)
1/2* x+2/3=9/2
1/2 * x = 9/2 - 2/3
1/2 * x= 23/6
x= 23/6 : 1/2
x= 23/6 x 2= 23/3
___
1/2*x-1/3=2/3
1/2*x = 2/3 + 1/3
1/2 * x= 1
x= 1: 1/2
x= 2
____
1/4+3/4:x=3
3/4 : x = 3 - 1/4
3/4 : x= 11/4
x= 11/4 : 3/4
x= 11/3
\(\dfrac{1}{2}\)\(\times\)\(x\) + \(\dfrac{2}{3}\) = \(\dfrac{9}{2}\)
\(\dfrac{1}{2}\)\(\times\)\(x\) = \(\dfrac{9}{2}\) - \(\dfrac{2}{3}\)
\(\dfrac{1}{2}\)\(\times\)\(x\) = \(\dfrac{23}{6}\)
\(x\) = \(\dfrac{23}{6}\):\(\dfrac{1}{2}\)
\(x\) = \(\dfrac{23}{3}\)
\(\dfrac{1}{2}\)\(\times\)\(x\) - \(\dfrac{1}{3}\) = \(\dfrac{2}{3}\)
\(\dfrac{1}{2}\)\(\times\)\(x\) = \(\dfrac{2}{3}\) + \(\dfrac{1}{3}\)
\(\dfrac{1}{2}\times\)\(x\) = 1
\(x\) = 1 : \(\dfrac{1}{2}\)
\(x\) = 2
\(\dfrac{1}{4}\) + \(\dfrac{3}{4}\): \(x\) = 3
\(\dfrac{3}{4}\): \(x\) = 3 - \(\dfrac{1}{4}\)
\(\dfrac{3}{4}\):\(x\) = \(\dfrac{11}{4}\)
\(x\) = \(\dfrac{3}{4}\): \(\dfrac{11}{4}\)
\(x\) = \(\dfrac{3}{11}\)
\(3\left(x-2\right)^2+9\left(x-1\right)=3\left(x^2+x-3\right)\\ \Leftrightarrow3\left(x^2-4x+4\right)+9x-9=3x^2+3x-9\\ \Leftrightarrow3x^2-12x+12+9x-9-3x^2-3x+9=0\\ \Leftrightarrow-6x+12=0\\ \Leftrightarrow x=2\)
\(3\left(x-2\right)^2+9\left(x-1\right)=3\left(x^2+x-3\right)\)
\(\Leftrightarrow3\left(x^2-4x+4\right)+9x-9=3x^2+3x-9\)
\(\Leftrightarrow3x^2-12x+12+9x-9-3x^2-2x+9=0\)
\(\Leftrightarrow-6x-6=0\)
\(\Leftrightarrow-6\left(x+1\right)=0\)
\(\Leftrightarrow x+1=0\)
\(\Leftrightarrow x=-1\)
Vậy phương trình có nghiệm là \(-1\)
2/3 = 2 x 4/ 3 x 4 =8/12
8/14 = 8 : 2/ 14 : 2 =4/7
5/9 = 5 x3/ 9 x 3 =15/37
35/ 40 = 35 : 5/ 40 : 5=7/8
Bài 1:
a) \(x.\dfrac{3}{4}=\dfrac{9}{14}\)
\(\Rightarrow x=\dfrac{9}{14}:\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{6}{7}\)
b) \(x:\dfrac{5}{9}=\dfrac{3}{10}\)
\(\Rightarrow x=\dfrac{3}{10}.\dfrac{5}{9}\)
\(\Rightarrow x=\dfrac{1}{6}\)
A) \(x-\dfrac{2}{3}=\dfrac{4}{5}\\ x=\dfrac{4}{5}+\dfrac{2}{3}\)
\(x=\dfrac{22}{15}\)
b)\(\dfrac{7}{9}-x=\dfrac{1}{3}\\ x=\dfrac{7}{9}-\dfrac{1}{3}\\ x=\dfrac{4}{9}\)
C)\(x:\dfrac{2}{3}=\dfrac{9}{8}\\ x=\dfrac{9}{8}x\dfrac{2}{3}\\ x=\dfrac{3}{4}\)
1) \(\left(x-3\right)^2-4=0\)
\(\Leftrightarrow\left(x-3-2\right)\left(x-3+2\right)=0\)
\(\Leftrightarrow\left(x-5\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=5\\x=1\end{matrix}\right.\)
2) \(x^2-2x=24\)
\(\Leftrightarrow x^2-2x-24=0\)
\(\Leftrightarrow x^2+4x-6x-24=0\)
\(\Leftrightarrow x\left(x+4\right)-6\left(x+4\right)=0\)
\(\Leftrightarrow\left(x+4\right)\left(x-6\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-4\end{matrix}\right.\)
1 sai
(a-b).(a+b)=a^2-b^2
2 đúng
3 đúng
4 sai
(x-3)^2=-(3-x)^2
5 sai
(x-3)^3=-(3-x)^3
Ta có: \(\left(x^2+3\right)^2-\left(x+3\right)\left(x-3\right)\left(x^2+9\right)\)
\(=x^4+6x^2+9-\left(x^2-9\right)\left(x^2+9\right)\)
\(=x^4+6x^2+9-x^4+81\)
\(=6x^2+90\)